In vivo evaluation of CNS depressant and antinociceptive activities of different extracts of trewia polycarpa leaves - Akter, Nahid (BRAC University, 2015)
This project report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2015.